The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1017/s0004972700018529
|View full text |Cite
|
Sign up to set email alerts
|

Proving a group trivial made easy: A case study in coset enumeration

Abstract: Dedicated to B.H. Neumann, on the occasion of his 90th birthdayCoset enumeration, based on the methods described by Todd and Coxeter, is one of the basic tools for investigating finitely presented groups. The process is not well understood, and various pathological presentations of, for example, the trivial group have been suggested as challenge problems. Here we consider one such family of presentations proposed by B.H. Neumann. We show that the problems are much easier than they first appear, albeit at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A number of comments on Theorem 1 are in order. The claim of finiteness of Γ depends upon coset enumeration, that was, for robustness purposes, carried out using two different implementations of the Todd-Coxeter algorithm: the built-in implementation of GAP system [10], and ACE implementation by G. Havas and C. Ramsay [13], also available as a GAP package [9]. Both computations in the case t = (3000), s = (2200) returned the index of the vertex stabiliser, the subgroup F := 3 4 :F 4 in the quotient Θ of the Coxeter group [3 2 , 4, 3 2 ] modulo the relations on Fig.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…A number of comments on Theorem 1 are in order. The claim of finiteness of Γ depends upon coset enumeration, that was, for robustness purposes, carried out using two different implementations of the Todd-Coxeter algorithm: the built-in implementation of GAP system [10], and ACE implementation by G. Havas and C. Ramsay [13], also available as a GAP package [9]. Both computations in the case t = (3000), s = (2200) returned the index of the vertex stabiliser, the subgroup F := 3 4 :F 4 in the quotient Θ of the Coxeter group [3 2 , 4, 3 2 ] modulo the relations on Fig.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Many of the problems were solved within 256 megabytes ofmain memory. This should be compared with the later experiments by Havas and Ramsay [12] [13] where an SGI Origin 2000 super computer was employed. That computer was equipped with more than 4 gigabytes of memory and could easily handle a coset table with 1 trillion table entries. Not only were results from the evolutionary algorithm on ACE achieved in a reasonable amount of time and space, it has been shown that the evolutionary algorithm described here can be used to verify existing hypothesizes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to enumerate billions of cosets [10], but such enumerations are computationally expensive. Hence, we use cheap filters to remove presentations which cannot define the desired group.…”
Section: Presenting a Group On Different Generating Setsmentioning
confidence: 99%